Refining Gen Z Listening Strategies with Spotify: A Comprehensive Guide - Nor, Hidayah (Universitas Nurul Jadid, 2025)
In an era marked by rapid technological advancement, honing effective listening skills is increasingly crucial for accurately absorbing information. To address this need, the current generation, particularly Gen Z'ers, can leverage contemporary applications like Spotify, a widely utilized music platform. Spotify offers global access to a vast library of music, serving as a valuable tool for enhancing listening abilities. This study investigates the impact of Spotify on the listening strategies of Gen Z'ers at UIN Antasari Banjarmasin, focusing on their independent learning practices and listening strategies while using the app. Employing Narrative Inquiry as the research method, interviews were conducted for data collection, with subsequent analysis using narrative analysis techniques. Findings revealed significant improvements in Gen Z'ers' metacognitive listening strategies across 5 categories including selective attention, directed attention, comprehension monitoring, real-time assessment of input, and comprehension evaluation after engaging with English songs utilized by participants, aiding in comprehension of complex English lyrics.